2018
DOI: 10.1017/s0022029918000262
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a synthetic analogue of the Bovine Appeasing Pheromone on milk yield and composition in Valdostana dairy cows during the move from winter housing to confined lowland pastures

Abstract: This Research Communication describes the effects of a synthetic analogue of the Bovine Appeasing Pheromone (BAP) on milk parameters in Valdostana dairy cows during the first turning out from tie-stalls to confined lowland pastures around the farms. Thirty healthy lactating Valdostana cows were enroled in the study and randomly divided into 2 groups: experimental group (EG, n = 15) and control group (CG, n = 15). The two groups were separately housed in the same farm and managed outside in two different pens. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 7 publications
2
10
0
Order By: Relevance
“…In our study, appeasing pheromones showed, after 30 days, a slight beneficial impact on bovine health, which is in line with previous studies [22,[24][25][26] also reporting an interest in using these molecules in cattle to improve animal health.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In our study, appeasing pheromones showed, after 30 days, a slight beneficial impact on bovine health, which is in line with previous studies [22,[24][25][26] also reporting an interest in using these molecules in cattle to improve animal health.…”
Section: Discussionsupporting
confidence: 92%
“…Among the potential alternatives, bovine appeasing pheromone is an attractive one. As stated above, several previous reports have shown a benefit when appeasing pheromones were used in dairy and beef cattle production [22,[24][25][26]. In our study, carried out in fattening units from western France using Charolais young bulls, we observed that significantly more clinical cases were detected on day 30 (D30) in the control group than in the group of bulls which received appeasing pheromone, while the opposite was observed earlier on D8.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…BAS has been used to reduce agonistic behavior in various animal species, thus stimulating feeding behavior and weight gain, and thus helped in improvement of post-weaning performance and reduced post-weaning mean haptoglobin concentrations. BAS administration helps in improved milk yield, reduced somatic cell count of dairy cows, and improved performance and reduced duration and costs of medication in case of pre-weaning dairy calves [35,36].…”
Section: Application Of Pheromones In Bovinesmentioning
confidence: 99%